Performance of Advanced Hybrid Link Adaptation Algorithms in Mobile Radio Channel - Vladimir, Wieser; Vladimir, Psenak (SPOLECNOST PRO RADIOELEKTRONICKE INZENYRSTVI, 2008)
The fast power adaptation is essential for WCDMA based mobile radio networks, as 3G UMTS. Although the first version of UMTS has been released in 1999 (Release 99) evolution was not finished yet. Quality of Service (QoS) and user data rate (e. g. HSDPA and HSUPA) are continuously increasing from release to release. Even though link adaptation frequency (1500 times per second) seems to be enough to span accidental fadings of mobile radio channel, used link adaptation algorithm is based on non-actual information about mobile radio channel state, which causes transmitter reaction delay to the actual channel state. Usage of appropriate prediction method to estimate near future channel state seems to be a valuable step to improve hybrid link adaptation algorithm. In this article we have described and simulated the new SIR-slot based advanced link adaptation algorithms. Algorithms were designed to increase efficiency of data transmission among a user equipment and base stations (uplink) for different simulation environments (pedestrian channel with mobile subscriber speed 5 km/h, 15 km/h and vehicular channel with speed 45 km/h).